Studies using the anti-idiotypic monoclonal antibody 105AD7 in patients with advanced and primary colorectal cancer - Maxwell-Armstrong, Charles Alan (1998)
Introduction. The anti-idiotypic monoclonal antibody 10SAD7 mimics the tumour associated antigen 791T/ gp72, present on approximately 80% of colorectal cancer cells. A Phase I study using 10SAD7 in 13 patients with advanced colorectal cancer has shown that it is nontoxic, and conferred a survival advantage on patients who received it [Denton GWL 1994]. Aim. There were two aims of this work. The first was to assess whether. the survival advantage seen in the Phase I study was reproducible in a Phase II study. The second was to immunise patients with primary colorectal cancer, in a non-randomised adjuvant study, and explore further the immune responses generated. Materials and Methods. Patients with advanced colorectal cancer were recruited to a randomised, double-blind, placebo controlled survival study. The first patient was recruited to this Phase II study in April 1994, and the last in October 1996. Four trial centres were used- Nottingham, Hull, Leeds, and Newcastle. Eligible patients had a life expectancy of 3 months, and none had received radiotherapy or chemotherapy in the preceding 1 and 3 months, respectively. Patients attended on 3 occasions, 6 weeks apart, receiving 10µg of 10SAD7/alum i.d. followed by 100µg i.m. Venous blood was assayed for blood count and differential, liver function, urea and electrolytes, and CEA. Chest X-rays and CT scans were performed at trial entry and week 12 where possible. Dates of death were recorded following consultation with General Practitioner or referring clinician. In addition, patients with primary colorectal cancer were recruited to a non-randomised adjuvant study, whereby they received 10SAD7 before surgery. Venous blood samples were taken between immunisation and operation, and assayed for lymphocyte subsets. Samples taken from resection specimens were analysed immunohistochemically. Fresh tumours were in addition disaggregated, and separated TIL labelled with a panel of monoclonal antibodies, and analysed by flow cytometry. Control tumours were similarly labelled. All analysis was performed blind. Results. 162 patients were randomised to the Phase II study, between April 1994 and October 1996. 85 received 105AD7 and 77 placebo. The mean ages and sex-ratios of the two groups were comparable, as was the time from diagnosis of advanced disease to trial entry (172v179 days). Median survival from date on study was 124 and 184 days, in 105AD7 and placebo arms, respectively (p=O.38). Survival from date of diagnosis of advanced disease was 456 and 486 days (p=O.82). Chemotherapy and radiotherapy all prolonged survival in a multivariate analysis. Only one serious adverse event was seen in the 105AD7 arm, and this was felt unlikely to be attributable to the vaccine. Twenty-four patients were recruited to the adjuvant study. Immunohistochemical analysis of tumour sections from 16 patients showed increased infiltration of CD4 and CD8 expressing lymphocytes, relative to a well matched control group (p<O.05). Infiltration of CD4, CD8 and CD56 expressing lymphocytes combined was significantly higher, as was that of the mitochondrial antigen 7A6, expressed on cells undergoing apoptosis (p<O.005). The activation marker CD25 was also significantly increased (p<O.05). Flow cytometric analysis of disaggregated tumours from 16 trial and 22 control patients, confirmed the increased expression of CD25 on TIL in the 105AD7 group (p<O.01). Peripheral blood phenotyping failed to show any significant increase in any lymphocyte subset, following immunisation. A separate analysis was performed comparing 2 year survival and recurrence in 23 patients immunised by the previous CRC Fellow, with 97 matched controls from the Trent Audit. No significant difference was seen between the two groups. Discussion. No survival difference was seen between patients receiving l05AD7 and placebo, in the Phase II study. This suggests that any immune responses generated by l05AD7 are insufficient to have a significant effect on tumour growth, in patients with advanced disease. Work has therefore focused on immunising patients with primary colorectal cancer. Patients receiving l05AD7 prior to resection of their primary tumours, showed an increased number of activated lymphocytes, and apoptosis, at the tumour site, relative to a well-matched control group. The numbers in the survival analysis based on patients recruited by the previous CRC fellow, are insufficient to show whether any of these immunological changes confer a survival advantage. This question can only be answered in a large, prospective, placebo-controlled study in patients with primary colorectal cancer.